Intradermal injection of incobotulinumtoxinA for face lifting - Rungsima Wanitphakdeedecha (2020)
© 2020 Wiley Periodicals LLC. Intradermal injection of botulinumtoxinA (BoNT/A) has been used off-label by many clinicians for the purpose of face-lifting effect. Some studies on AbobotulinumtoxinA (AboA) demonstrated clinical efficacy on face-lifting effect when comparing to normal saline solution (NSS). So far, there is no split-face comparison study on face-lifting effect of IncobotulinumtoxinA (IncoA). The objective of this study was to compare the face-lifting effect of IncoA intradermal injection and NSS. Twenty-two subjects were enrolled and randomly injected with IncoA at 1:6 cc dilution (100 unit or 1 vial in 6 cc of NSS) on one side, and NSS on the other side by using intradermal injection technique. Standardized photographic documentation with 2-, and 3-dimentional imaging system (Vectra H1, Canfield Scientific, Inc., Fairfield, NJ) were obtained at baseline, and at 2 weeks after treatment. The face-lifting effect was graded by the subjects and two blinded dermatologists, using photographic comparison. Side effects were also recorded at the end of the study. Immediate face-lifting was identified on the side that was treated with IncoA by blinded injectors in 63.6% of patients. Of all subjects, 17 (77.3%) have noticed the improvement of skin laxity on the side that was treated with IncoA at 2 weeks after treatment. The difference in facial contouring volume measured by Vectra H1 imaging system on IncoA side was significantly higher (P =.033) when comparing to NSS side in patients aged <36 years old. However, there was no statistically significant difference in face-lifting when comparing between IncoA and NSS evaluated by two blinded dermatologists (P = 1.00). Facial asymmetry was found in 36.4% of subjects. This study demonstrated the face-lifting effect of IncoA intradermal injection. Further studies with larger number of subjects and proper method of evaluation should be done to verify these findings.